A novel fluorescent sensor based on aptamer recognition and DNA walker amplification strategy and its determination of 17β-estradiol - Yajun Zhang; Licong Jia; Wei Wang; Meng Jiang; Hongying Zhang; LingMei Niu (Arabian Journal of Chemistry, 2023)
17β-Estradiol (E2) is a common environmental endocrine and excessive estrogen will disturb the endocrine balance of human body and lead to diseases because of its accumulation in human body. The main aim of this study is to determine the trace amount of E2 in various foods. Based on aptamer specific recognition, DNA walker molecular machine and Exonuclease III-assisted dual cycle signal amplification technology, a fluorescent aptamer sensor was constructed and applied to the detection of 17β-estradiol. Atomic force microscopy (AFM) and polyacrylamide gel electrophoresis (PAGE) were used to verify the feasibility of DNA walker participating in the reaction. Under the optimal conditions, 17β-estradiol concentration showed a good linear relationship with fluorescence in the range of 5.0 × 10−10–1.8 × 10−8 M, and the detection limit was 5.6 × 10−11 M. The fluorescent aptamer sensor established in this study has good selectivity, simple operation and good specificity, and the results of its application in the determination of milk samples are satisfactory. Research findings revealed that the E2 concentration in water and milk is less than the safe limits, indicating the foods in the market are safe and can be consumed. Though the foods are safe in present content, the health risk still exists because of continuous intake of trace E2.